Fundamentals of oceanography - Sverdrup, Keith A. (McGraw-Hill Higher Education, 2006)
"Fundamentals of Oceanography" is intended for less intensive college oceanography courses, and courses for non-science majors. To meet the needs of these groups, this text has numerous student aids including chapter learning objectives, section review questions, summary charts, units in metric and English units, chapter summaries, chapter word lists, bold face for technical terms in the text, and reduced use of technical terms. No prerequisites in math, chemistry, physics, or biology are required.